Push a novel - Sapphire 1950- (Vintage Contemporaries/Vintage Books, 1997)
Relentless, remorseless, and inspirational, this "horrific, hope-filled story" ("Newsday") is certain to haunt a generation of readers. Precious Jones, 16 years old and pregnant by her father with her second child, meets a determined and highly radical teacher who takes her on a journey of transformation and redemption.